KAJIAN PEMUDA KARANG TARUNA DALAM MENINGKATKAN PEMBANGUNAN MASYARAKAT DI DESA SOAKONORA KECAMATAN JAILOLO KABUPATEN HALMAHERA BARAT - Lainsamputty, Gerald B.; Lumintang, Juliana; Kawung, Evelin J.R. (Universitas Sam Ratulangi, 2019)
Study of Soakonora village of Karang Taruna Programs that have been realized since the year 2018 and to enhance community development (social welfare) in the village of Soakonora. Such activities (football and volleyball) in which children, youth and women. Participated to activities undertaken Karang Taruna Soakonora Village. On certain programs can be done with a conducive, in the village Karang Taruna learn Soakonora (Karang Taruna Youth Training, supervision and create an inherent good working environment). Chairman (Chairman) to all members of the Organization of Karang Taruna Village Soakonora so what is expected of the parties supporting the head Village/Soakonora Village Karang Taruna Builder, religious figures and community leaders the activities can be realized. The program distributed Karang Taruna to the Community-is very big impact and nothing is unmatched from Karang Taruna in other villages. This activity became a Community feel Life Guidelines of development, due to a social welfare which can reduce inequalities-inequalities which exist in the community, basically a youth who belongs to the Karang Taruna Village Soakonora capable of organizing the social welfare problem (Hijinks, free sex, Booze and Brawl. Therefore the Government authorize Village organizational karangtaruna are able to accomplish what is becoming the responsibility of the Youth pioneers the true Young Blood, tough, courageous, Honest and Act for the sake of ideals a nation's future Optimistic. Thus KarangTaruna the village Soakonora is a form of overriding high honor by the Government of the Village where it has been successful and the realization of the program due to the construction of a community around and created a Harmony and Creativity is intact. Keyword: Karang Taruna, youth, organization